The Psychological Effects of Exergames for Children and Adolescents with Obesity: A Systematic Review and Meta-Analysis - Correia C.K.* (2019)
© 2019, Mary Ann Liebert, Inc.The systematic review and meta-analysis were conducted to analyze the psychological effects of exergames for children and adolescents with overweight or obesity. In August 2018, the electronic databases searched were PubMed, Scopus, Web of Science, SPORTDiscus, Science Direct, CINAHL, and PsycINFO. The eligibility criteria were defined according to the population, intervention, comparison, outcome, and study design. In relation to the population, only studies with children or adolescents with overweight or obesity and without any other comorbidities were analyzed. Only publications in English were considered. Nine studies were selected. The comparisons identified were in relation to weight, type of activity, and play style versus control and preintervention. The magnitude of effect size suggests that the practice of exergaming has a small effect on psychological outcomes. Furthermore, cooperative games produced greater attraction to the game (g = 4.71, 95% confidence interval [CI] = 3.23-6.19) and greater intrinsic motivation (g = 5.29; 95% CI = 3.68-6.90). It was verified that self-esteem (standard mean difference [SMD] = 0.37; 95% CI = 0.09-0.66), and self-efficacy (SMD = 0.42; 95% CI = 0.06-0.79) improved after playing an exergame. This systematic review and meta-analysis suggest that exergames may be effective in improving psychological aspects of children and adolescents with overweight or obesity. Given the limited number of studies, it is essential to increase scientific research in this area.